Importance of cortactin for efficient epithelial NF-kappa B activation by Helicobacter pylori, Salmonella enterica and Pseudomonas aeruginosa, but not Campylobacter spp. - Tegtmeyer-Backert, Nicole; Soltan Esmaeili, Delara; Sharafutdinov, Irshad; Knorr, Jakob; Naumann, Michael; Alter, Thomas; Backert, Steffen (European Journal of Microbiology and Immunology, 2021)
Transcription factors of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappa B) family control important signaling pathways in the regulation of the host innate immune system. Various bacterial pathogens in the human gastrointestinal tract induce NF-kappa B activity and provoke pro-inflammatory signaling events in infected epithelial cells. NF-kappa B activation requires the phosphorylation-dependent proteolysis of inhibitor of kappa B (I kappa B) molecules including the NF-kappa B precursors through ubiquitin-mediated proteolysis. The canonical NF-kappa B pathway merges on I kappa B kinases (IKKs), which are required for signal transduction. Using CRISPR-Cas9 technology, secreted embryonic alkaline phosphatase (SEAP) reporter assays and cytokine enzyme-linked immunosorbent assay (ELISA), we demonstrate that the actin-binding protein cortactin is involved in NF-kappa B activation and subsequent interleukin-8 (IL-8) production upon infection by Helicobacter pylori, Salmonella enterica and Pseudomonas aeruginosa. Our data indicate that cortactin is needed to efficiently activate the c-Sarcoma (Src) kinase, which can positively stimulate NF-kappa B during infection. In contrast, cortactin is not involved in activation of NF-kappa B and IL-8 expression upon infection with Campylobacter species C. jejuni, C. coli or C. consisus, suggesting that Campylobacter species pluralis (spp.) induce a different signaling pathway upstream of cortactin to trigger the innate immune response.
CRIS-Team WoS Importer:2022-02-25
Keywords: ADP-heptose; NF-ĸB; Helicobacter pylori; T4SS; cortactin; Src; interleukin-8; inflammation